2017
DOI: 10.15330/pcss.18.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Sorption Parameters of Nickel Ions on Bentonite in the Result of its Irradiation by Microwaves

Abstract: The adsorption isotherms of nickel ions from aqueous solutions on bentonite, a natural argillaceous material, previously prepared using ultrahigh-frequency electromagnetic waves ("microwaves") were researched in the article. The phase composition of the sorbent was studied by applying the X-ray powder method. Bentonite sample being pre-wetted and irradiated by microwaves shows 2.7 times better sorption properties than the untreated (native) sample, which was shown on the example of the adsorption process of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
4
0
5
Order By: Relevance
“…The maximal adsorption capacities represent the adsorbent affinity towards copper ions. The results of the present study and the data from our previous investigations have shown that direct irradiation to bentonite (DIR) [20,22,23] is more advantageous than the procedure for two-step activation of the sorbent (STIM) [19,21,24] because it does not require an additional stage of treatment of the sorbent (preliminary washing with double distillated water during irradiation). A smaller amount of technological operations simplify the process, reduce time and, accordingly, reduce the cost of water treatment.…”
Section: Adsorption Of Coppermentioning
confidence: 77%
See 3 more Smart Citations
“…The maximal adsorption capacities represent the adsorbent affinity towards copper ions. The results of the present study and the data from our previous investigations have shown that direct irradiation to bentonite (DIR) [20,22,23] is more advantageous than the procedure for two-step activation of the sorbent (STIM) [19,21,24] because it does not require an additional stage of treatment of the sorbent (preliminary washing with double distillated water during irradiation). A smaller amount of technological operations simplify the process, reduce time and, accordingly, reduce the cost of water treatment.…”
Section: Adsorption Of Coppermentioning
confidence: 77%
“…Maximum adsorption capacity of heavy metal ions (mg/g) a Ni [19] b Ni [20] a Zn [21] b constant weight was reached. The content of Cu 2+ ions in solutions was determined by the atomic absorption method.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Автори уже повідомляли у своїх попередніх публікаціях [5][6][7][8][9][10][11] про результати вивчення сорбційних властивостей глинистого матеріалу бентоніту (Бнт), опроміненого мікрохвилями у поєднанні з гідротермальною активацією. Було з'ясовано, що здатність цього природного сорбенту вилучати з водних розчинів деякі ВМ (зокрема, йони свинцю, міді, цинку та нікелю) помітно зростає після такої комбінованої підготовки.…”
Section: вступunclassified